2010
DOI: 10.1161/circulationaha.110.992552
|View full text |Cite
|
Sign up to set email alerts
|

Primary Results From the SmartDelay Determined AV Optimization: A Comparison to Other AV Delay Methods Used in Cardiac Resynchronization Therapy (SMART-AV) Trial

Abstract: Background-One variable that may influence cardiac resynchronization therapy response is the programmed atrioventricular (AV) delay. The SmartDelay Determined AV Optimization: A Comparison to Other AV Delay Methods Used in Cardiac Resynchronization Therapy (SMART-AV) Trial prospectively randomized patients to a fixed empirical AV delay (120 milliseconds), echocardiographically optimized AV delay, or AV delay optimized with SmartDelay, an electrogram-based algorithm. Methods and Results-A total of 1014 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 368 publications
(151 citation statements)
references
References 47 publications
(54 reference statements)
2
141
1
7
Order By: Relevance
“…Echocardiographic optimization of atrioventricular delays in CRT patients can alleviate HF symptoms and increase exercise capacity compared with nominal programming, particularly when approaching nonresponding populations [68]. However, echocardiographic optimization in the PROSPECT study did not support this approach in a randomized trial, and the Frequent Optimization Study Using the QuickOpt Method (FREEDOM) trials failed to provide evidence supporting the benefit of CRT optimization and did not demonstrate superiority of the respective algorithms over nominal or empiric programming [69][70][71]. There are limited data supporting the use of LV-only stimulation in a small subset of patients who fail to respond to biventricular stimulation [72].…”
Section: Cardiac Resynchronization Therapy: Consistent Delivery Of Vementioning
confidence: 99%
“…Echocardiographic optimization of atrioventricular delays in CRT patients can alleviate HF symptoms and increase exercise capacity compared with nominal programming, particularly when approaching nonresponding populations [68]. However, echocardiographic optimization in the PROSPECT study did not support this approach in a randomized trial, and the Frequent Optimization Study Using the QuickOpt Method (FREEDOM) trials failed to provide evidence supporting the benefit of CRT optimization and did not demonstrate superiority of the respective algorithms over nominal or empiric programming [69][70][71]. There are limited data supporting the use of LV-only stimulation in a small subset of patients who fail to respond to biventricular stimulation [72].…”
Section: Cardiac Resynchronization Therapy: Consistent Delivery Of Vementioning
confidence: 99%
“…In a sub-study of the SMART AV trial [101], patients were again dichotomized, although this time according to the median Q-LV value (95 ms). Gold et al showed that implanting the LV lead at a site with a favorable Q-LV was independently associated with symptomatic improvement and greater reverse remodeling at 6 months [19].…”
Section: Identifying the Site Of Latest Electrical Activation (Lea)mentioning
confidence: 99%
“…Un pequeño estudio aleatorizado y algunas series de observación han mostrado mejorías significativas de los síntomas de IC y hospitalizaciones por IC después de optimizar los retrasos AV o VV 74,75,w134-w143 , sobre todo en pacientes con IC isquémi-ca w144 . Estos hallazgos no se confirmaron con los resultados de estudios multicéntricos más amplios [76][77][78][79][80][81][82][83] , lo que indica que optimizar sistemáticamente el retraso VV y AV tiene poco efecto en los resultados clínicos o ecocardiográficos obtenidos por quienes reciben TRC, en comparación con un retraso AV fijo de 100-120 ms y estimulación cardiaca biventricular (VD y VI) simultánea (tabla web 12). La selección del paciente, los tiempos del procedimiento y la metodología empleada (algoritmos de dispositivo, ECG o ecocardiografía) no fueron homogéneos entre todos los estudios, lo que impide obtener conclusiones firmes.…”
Section: Optimización Del Dispositivo De Terapia De Resincronización unclassified
“…web 9). Se han propuesto varios métodos para optimizar el retraso AV y VV (tabla 13) [74][75][76][77][78][79][80][81][82][83] . Estos métodos pueden clasificarse en dos grupos principales: métodos basados en la ecocardiografía y no basados en la ecocardiografía.…”
Section: Optimización Del Dispositivo De Terapia De Resincronización unclassified